PERANAN GAMELAN SEBAGAI PENGIRING WAYANG KULIT DI GROUP KRIDO LARAS KOTA MEDAN - Helen Kurnia Sitinjak (Grenek: Jurnal Seni Musik, 2013)
This study aims to determine the development the role gamelan as accompainist wayang kulit di Group Krido Laras Kota Medan. Method in this study uses a qualitative description of the method in which the data is examined through interviews, data collection in the form books, scientific papers, and electronic materials based on topics of research material. The study chose location at Sanggar Musik Campursari Group Krido Laras di Jalan Bromo No. 26 Kota Medan. The population in this study were taken 1 dalang, 3 pesinden dan 13 music performer and informants related to being this research study.After analysis, it was found that results of Group Krido Laras was esthabilised in 2000. The Group Krido Laras one music group that still maintains the traditional gamelan musical instruments as accompaniment shadow puppets. The Group Krido Laras in the city of Medan actually exist and still active to perform a shadow puppet performances accompanied by gamelan. In this case the Group Krido Laras is taken as the study sample for this thesis because this group is a group whose that still maintains gamelan as accompanist shadow puppets in the city of Medan.